2016
DOI: 10.1016/j.joca.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for meniscal body extrusion on MRI in subjects free of radiographic knee osteoarthritis: longitudinal data from the Osteoarthritis Initiative

Abstract: Only female sex, incident meniscal tear, and higher baseline value of extrusion are risk factors for increased meniscal body extrusion in subjects free of radiographic OA. The results suggest that meniscal extrusion may contribute to and mediate the well-known increase in knee OA incidence in middle-aged women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 34 publications
4
36
0
Order By: Relevance
“…At large, we found that women without OA had similar degree of meniscal body extrusion and cartilage coverage as men without OA. We further corroborate previous findings that the presence of ipsilateral meniscus damage was associated with meniscal extrusion in the medial compartment [8, 15, 17, 18, 2325, 32–34]. Similar to prior reports, our cross-sectional data cannot answer the question whether meniscus damage, typically consisting of horizontal cleavages and/or flap tears (or in elderly women, simply meniscus maceration/destruction), is a result of a more mobile meniscus, or if the extrusion and displacement are a result of an already damaged meniscus and potentially disrupted hoop-tension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At large, we found that women without OA had similar degree of meniscal body extrusion and cartilage coverage as men without OA. We further corroborate previous findings that the presence of ipsilateral meniscus damage was associated with meniscal extrusion in the medial compartment [8, 15, 17, 18, 2325, 32–34]. Similar to prior reports, our cross-sectional data cannot answer the question whether meniscus damage, typically consisting of horizontal cleavages and/or flap tears (or in elderly women, simply meniscus maceration/destruction), is a result of a more mobile meniscus, or if the extrusion and displacement are a result of an already damaged meniscus and potentially disrupted hoop-tension.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to prior reports, our cross-sectional data cannot answer the question whether meniscus damage, typically consisting of horizontal cleavages and/or flap tears (or in elderly women, simply meniscus maceration/destruction), is a result of a more mobile meniscus, or if the extrusion and displacement are a result of an already damaged meniscus and potentially disrupted hoop-tension. However, a prior longitudinal report based on Osteoarthritis Initiative data has provided evidence in support of the latter [25]. Either way, a damaged and extruded meniscus can no longer optimally fulfill its main purpose to distribute loads on the surrounding hyaline cartilage surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Englund et al showed that a higher BMI is related to meniscal extrusion, although this was not confirmed in another study sample 3,4 . Since obesity is modifiable, one can hypothesize that losing weight might reduce or reverse extrusion, thus preventing development or progression of knee OA.…”
Section: Discussionmentioning
confidence: 83%
“…It can occur secondary to meniscal tears 2,3 , but multiple other factors are related to extrusion, including higher age, obesity, history of knee trauma, malalignment and generalized osteoarthritis (OA) 4,5 . The generally accepted idea is that a displaced meniscus affects the weight-bearing and load distribution capacities within the knee joint, which leads to loss of cartilage and increase in bone marrow lesions, ultimately resulting in knee OA [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…This was also shown in other studies. (20,21) Meniscal extrusion was also seen with higher frequency in those patients with a history of trauma (36.8%) in contrast to those without trauma (9.1%).…”
Section: Discussionmentioning
confidence: 99%